A Study to Assess the Knowledge and Attitude Regarding Weaning among Mothers of Infants in selected Rural Area at Rohtak with a View to Develop an Information Booklet on Weaning (International Journal of Nursing Education, 2021)
Introduction: Weaning is that the most important amount for the expansion of the kid. this canbe the time once growth faltering and organic process deficiencies manifest in youngsters. Weaning,a shift amount from breast-feeding to adult diet is sometimes related to variety of issues and issues indeveloping countries. the main issues area unit what foods ought to lean to the kid, however and afterthey ought to lean. The age to introduce a lactation foods varies and is influenced by the tradition of thevarious ethnic population within the country, urbanization and therefore the socioeconomic standing ofhouseholds Objectives of the study: To assess the information of mothers of infants relating to a lactation.To assess the perspective of mothers of infants relating to a lactation. To develop associate data leaflet.Material and Methods: The scientist conducted the study exploitation quantitative approachand non- experimental style on a hundred mothers of infants by non likelihood convenientsampling technique. Structured form was accustomed assess the information of mothers of infantsand perspective list was accustomed assess the perspective of mothers of infants relating to alactation. Descriptive and inferential statistics accustomed analyze the info. Results: The norm of takea look at information score and perspective was fifteen.4 and 9.45respectively. None of mothersof infants had inadequate information, thirty first had moderate information and sixty nine hadadequate information relating to a lactation. Majority of samples that’s ninety eight of mothers ofinfants had favorable perspective, and solely two mothers had unfavorable perspective relating tolactation. There was vital correlation between information and perspective of mothers of infants relatingto lactation. Conclusion: The investigator finished that the information of the mothers of infants isadequate. And there’s vital correlation between information and perspective of mothers of infants relatingto a lactation. {the information the information |the data} leaflet can facilitate in up the knowledge ofmothers of infants relating to a lactation